Alleviation of seeding chlorosis by plant growth regulators in drip-irrigated rice. (17th February 2017) - Zhang, Jun; Zhang, Shujie; Chen, Lin; Wei, Changzhou
ABSTRACT: Drip irrigation can produce high rice yields with significant water savings; therefore, it extends rapidly in water-scarce northern China. However, drip-irrigated rice seedlings often exhibit Fe chlorosis. The objective of this field experiment was thus to determine the ability of plant growth regulators to alleviate chlorosis in drip-irrigated rice seedlings. The study compared three plant growth regulators (1-naphthylacetic acid, NAA; sodium nitrophenolate, CSN; and diethyl aminoethyl hexanoate, DA-6) applied in two ways (seed-soaking and drip-application). The results showed that CSN increased root oxidation activity by 37% in the seed-soaking treatment and by 45% in the soil-application treatment. Seed soaking with NAA, CSN, and DA-6 increased the active Fe content in leaves by 8.8%, 17.5%, and 11.4%, respectively, compared with untreated seedlings. Iron absorption and SPAD values were both greater in the soil-application plots than in the seed-soaking plots. Among the plant growth regulators, CSN resulted in the highest yield (2.2% greater than untreated rice in the seed-soaking treatment and 12.8% greater than untreated rice in the soil-application treatment). In conclusion, CSN significantly improved root Fe uptake at the seedling stage and reduced chlorosis in drip-irrigated rice. Therefore, CSN drip application can be recommended for alleviating rice chlorosis in practical use.